2021
DOI: 10.3389/fmed.2020.630880
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Optical Coherence Tomography Angiography Retinal Alterations in Patients With Nasopharyngeal Carcinoma

Abstract: Aim: The aim of the study was to investigate the early neurovascular alterations of the retina in radiation encephalopathy (RE) patients with normal-ranged visual acuity after radiotherapy for nasopharyngeal carcinoma.Methods: Fifty-five RE patients and 54 healthy age-matched subjects were enrolled in this retrospective cross-sectional case–control study. The best corrected visual acuity (LogMAR) of the included eye should not be more than 0. The vessel density and thickness of different locations in the retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Most VD and retinal thickness indexes in the macular and ONH areas were significantly reduced in RON compared to NRON, which means that the RON patients included in our study had an overall serious condition, as neural and microvascular impairments emerged throughout the fundus. In a previous study, 7 NRON and healthy controls were compared, and a significant reduction in VD and thickness existed in NRON but was not as distinct as that between RON and NRON in this study. It is possible to be involved in a progressive, irreversible atrophy process after radiation, even for a long time.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Most VD and retinal thickness indexes in the macular and ONH areas were significantly reduced in RON compared to NRON, which means that the RON patients included in our study had an overall serious condition, as neural and microvascular impairments emerged throughout the fundus. In a previous study, 7 NRON and healthy controls were compared, and a significant reduction in VD and thickness existed in NRON but was not as distinct as that between RON and NRON in this study. It is possible to be involved in a progressive, irreversible atrophy process after radiation, even for a long time.…”
Section: Discussioncontrasting
confidence: 50%
“…6 RON is more likely to occur in NPC patients with radiation encephalopathy (RE) because the onset of RE may mean a higher dose and a more serious degree in the patients. A previous study 7 showed that the visual field (VF) and retinal vessels were impaired even in RE patients with normal-range visual acuity. Moreover, most RE patients usually refer to the neurology clinic for their initial symptoms, such as headaches, dizziness and dementia.…”
Section: Introductionmentioning
confidence: 98%